Reversible Self-Assembled Monolayers (rSAMs) as Robust and Fluidic Lipid Bilayer Mimics - Yeung, Sing Yee (Langmuir : the ACS journal of surfaces and colloids, 2018)
Lipid bilayers, forming the outer barrier of cells, display a wide array of proteins and carbohydrates for modulating interfacial biological interactions. Formed by the spontaneous self-assembly of lipid molecules, these bilayers feature liquid crystalline order, while retaining a high degree of lateral mobility. Studies of these dynamic phenomena have been hampered by the fragility and instability of corresponding biomimetic cell membrane models. Here, we present the construct of a series of oligoethylene glycol-terminated reversible self-assembled monolayers (rSAMs) featuring lipid-bilayer-like fluidity, while retaining air and protein stability and resistance. These robust and ordered layers were prepared by simply immersing a carboxylic acid-terminated self-assembled monolayer into 5-50 μM aqueous ω-(4-ethylene glycol-phenoxy)-α-(4-amidinophenoxy)decane solutions. It is anticipated that this new class of robust and fluidic two-dimensional biomimetic surfaces will impact the design of rugged cell surface mimics and high-performance biosensors